Validating the Smart Grid Architecture Model for Sustainable Energy Community Implementation: Challenges, Solutions, and Lessons Learned - Janev, Valentina; Berbakov, Lazar; Tomašević, Nikola; Sotoca, Jesús Martin-Borja; Lujan, Sergio (Energies (Basel), 2025)
The integration of renewable energy sources (RESs) and the establishment of energy communities (ECs) are vital steps in achieving global sustainability goals. This paper presents a methodology for developing and validating a Smart Grid Architecture Model (SGAM)-compliant software platform designed to integrate data-driven energy services and connect physical energy assets within energy communities. The platform aims to optimize energy dispatch, enhance self-consumption, and facilitate interoperability with smart grid infrastructures. Two case studies—Polígono Industrial Las Cabezas in Spain and the IMP R&D campus in Serbia—are analyzed to highlight real-world challenges, solutions, and lessons learned. The article points to different scenarios relevant for energy community design and implementation. Lessons learned point to challenges related to device integration, production forecasting, user engagement, and regulatory barriers. The results show that the proposed SGAM platform successfully addresses technical and operational complexities, supporting energy efficiency, decarbonization, and scalability.